New Species of Oochoristica Lühe, 1898 (Cestoda: Linstowiinae) from Sceloporus ochoterenae (Reptilia: Sauria: Phrynosomatidae) in Central Mexico: Approach to the Phylogenetic Relationships of the Genus with Molecular Evidence - Velázquez-Brito Andrés; García-Prieto, Luis; de Oca Uriel Garduño-Montes; León-Règagnon, Virginia (Acta parasitologica, 2025)
PurposeTo describe a new species of Oochoristica Lühe, 1898, an anoplocephalid cestode included in Linstowiinae (Cyclophyllidea), parasitizing Sceloporus ochoterenae Smith in Zoyatepec, Guerrero, Mexico.MethodsAll specimens were fixed with 4% hot formalin. A morphologic study was made using stained material under light microscopy. Some specimens of a second species (collected in Sceloporus grammicus from La Malinche, Tlaxcala, fixed in 100% ethanol, were also stained and studied morphologically; others were subject of DNA sequencing and phylogenetic analysis.ResultsA new species of this genus is described of the intestine of an endemic lizard S. ochoterenae. Oochoristica guerreroensis n. sp. shares a distinctive morphological feature (mature proglottids wider than long) with only 13 species of genus. However, O. guerreroensis n. sp. can be differentiated by: strobilar size (4.29–7.62 mm), number of testes (48–55), shape of vitellaria (ovoid) and number of ovarian sublobes (3–5), as well as by their geographical distribution (Neotropical region of Mexico), and type of host. Based on molecular evidence of nuclear 28S rDNA gene, we analyze for the first time the phylogenetic position of one species of Oochoristica (O. scelopori) within Anoplocephalidae as well as their relationships with other genera of Cyclophyllidea.ConclusionsThe new species is the first described in association with a phrynosomatid lizard in the Neotropical realm, and the ninth recorded in Mexico. Molecular data obtained in our study seem to confirm the independence Oochoristica and Mathevotaenia.